Is healthy food affordable in Surkhet, Nepal? Cost and affordability of a healthy diet - Chauhan, Alka; Tomar, Anindya; Headey, Derek D.; Scott, Samuel P.; Kishore, Avinash; Menon, Purnima (CGIAR System Organization, 2024)
The Transforming Agrifood Systems in South Asia (TAFSSA) local food systems assessment aims to provide a reliable, accessible and integrated evidence base that links farm production, market access, dietary patterns, climate risk responses, and natural resource management with gender as a cross-cutting issue in rural areas of Bangladesh, India, and Nepal. It was designed to be a district-level multi-year assessment. Using data collected in March-April 2023, this data note describes household spending behavior on foods, share of food groups in cost of healthy diet, and how much money households have to spend to achieve a healthy diet. This is one of a set of data notes that, together, provide a holistic picture of the agrifood system in the district.